Formação Profissional na Escuela de Trabajo Social da Universidad de Costa Rica - Carvalho, Debora de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This monograph brings the debate on the professional training of the Escuela de Trabajo Social da Universidad de Costa Rica (UCR) today and its theoretical and political orientation. The study presented here was part of a broader research, which studied in the years 2018 and 2019 the theoretical trends of Social Work in Latin America, specifically in six countries: Costa Rica, Cuba, Argentina, Paraguay, Uruguay and Chile. This research was based on secondary and primary sources, secondary data included bibliographic material and analysis of documents, this highlights the analysis of three UCR undergraduate final papers produced mainly in the 2000s; primary in the collection of empirical data, which took place through semi-structured interviews with the course coordinator and with two students that made up the Escuela de Trabajo Social in 2019: one for the fourth year and one for the fifth year. The interviews were carried out in loco by the researcher who visited the country in the first two weeks of August 2019. It was found that social work in Costa Rica, and specifically, at UCR has an eclectic character, where theoretical trends are expressed as emphases, such as: assistance, socio-educational, promotional, therapeutic and managerial. That is, even if there is a concern for training at the UCR to be generalist and committed to a critical approach to social reality, it is clear that there is a defense that activities specific to the profession must be treated with different theoretical contributions, and that therefore follow as a reference in the training process. In this, it is highlighted that in this study the analysis the constitution and characteristics of the State of Costa Rica, public policies and their relations with the genesis and development of the social work in Costa Rica and the dynamics of the UCR was essential for the apprehension of the direction of the professional training of the course of work social at UCR.

Esta monografia traz o debate sobre a formação profissional da Escuela de Trabajo Social da Universidad de Costa Rica (UCR) atualmente e seu direcionamento teórico político. O estudo aqui apresentado fez parte de uma pesquisa mais ampla, que estudou nos anos de 2018 e 2019 as tendência teóricas do Serviço Social na América Latina, especificamente em seis países: Costa Rica, Cuba, Argentina, Paraguai, Uruguai e Chile. Esta pesquisa se fundamentou em fontes secundárias e primárias, os dados secundários incluíram material bibliográfico e análise de documentos, nisto destaca-se a análise de três trabalhos finais de graduação da UCR produzidos, sobretudo, nos anos 2000; os primários na coleta de dados empíricos, a qual se deu por meio de entrevistas semi-estruturadas com a coordenadora do curso e com dois discentes que compunham em 2019 a Escuela de Trabajo Social: uma do quarto ano e um do quinto ano. As entrevistas foram feitas in loco pela pesquisadora que visitou o país nas duas primeiras semanas de agosto de 2019. Constatou-se que o trabajo social em Costa Rica e, especificamente, na UCR possui um caráter eclético, onde as tendências teóricas se expressam como ênfases, tais como: assistencial, socioeducativa promocional, terapêutica e gerencial. Ou seja, ainda que haja uma preocupação para que a formação na UCR seja generalista e comprometida com uma abordagem crítica da realidade social, percebe-se que há a defesa de que as atividades específicas da profissão devem ser tratadas com aportes teóricos diferentes, e que portanto seguem como referência no processo de formação. Nisto, destaca-se que neste estudo a análise da constituição e características do Estado de Costa Rica, das políticas públicas e suas relações com a gênese e desenvolvimento do trabajo social em Costa Rica e da própria dinâmica da UCR foi essencial para a apreensão do direcionamento da formação profissional do curso de trabajo social na UCR.
Professional Training at the School of Social Work of the Universidad de Costa Rica
Keywords: Trabajo Social; Professional Qualification; Social Work; Formação Profissional; Costa Rica